2014
DOI: 10.3109/14767058.2014.964676
|View full text |Cite
|
Sign up to set email alerts
|

Endocan, a putative endothelial cell marker, is elevated in preeclampsia, decreased in acute pyelonephritis, and unchanged in other obstetrical syndromes

Abstract: Objective: Endocan, a dermatan sulphate proteoglycan produced by endothelial cells, is considered a biomarker for endothelial cell activation/dysfunction. Preeclampsia is characterized by systemic vascular inflammation, and endothelial cell activation/dysfunction. Therefore, the objectives of this study were to determine whether: (1) plasma endocan concentrations in preeclampsia differ from those in uncomplicated pregnancies; (2) changes in plasma endocan concentration relate to the severity of preeclampsia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 234 publications
(139 reference statements)
2
35
1
Order By: Relevance
“…Its synthesis and release of this molecule are raised by proinflammatory cytokines such as tumor necrosis factor (TNF)‐α and interleukin 1B [7]. In numerous studies (hepatocellular [8], renal cancers, lung, breast [9–11], acute myeloid leukemia [22], preeclampsia [12,13], acute migraine attack [23], obstructive sleep apnea [24]) Endocan levels were found to be high. In addition, it is also mentioned in these studies that Endocan can be a diagnostic and prognostic factor in pulmonary diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its synthesis and release of this molecule are raised by proinflammatory cytokines such as tumor necrosis factor (TNF)‐α and interleukin 1B [7]. In numerous studies (hepatocellular [8], renal cancers, lung, breast [9–11], acute myeloid leukemia [22], preeclampsia [12,13], acute migraine attack [23], obstructive sleep apnea [24]) Endocan levels were found to be high. In addition, it is also mentioned in these studies that Endocan can be a diagnostic and prognostic factor in pulmonary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Its synthesis is induced by pro‐inflammatory cytokines [7]. Endocan levels were found to be high in many diseases particularly in lung [8], renal cancers [9–11], preeclampsia [12,13], in which Endocan could be used as the biomarker. It is also mentioned that Endocan may have a diagnostic and prognostic role in pulmonary diseases [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…250 Circulating endothelial cells and other markers of endothelial activation/injury such as soluble VCAM-1, E-selectin and endocan are increased in preeclamptic compared with normal pregnant women. 149,184,260,261 Other studies have shown a decrease in circulating endothelial progenitor cells as a marker of endothelial damage in preeclamptic women. 262 …”
Section: Mmps and Vascular Dysfunction In Hypertensive Pregnancy Amentioning
confidence: 99%
“…Studies have shown an increase in CEC number and other markers of EC damage such as soluble vascular cell adhesion molecule-1 (sVCAM-1), E-selectin and endocan in PE compared with Norm-Preg women (Canbakan et al, 2007; Adekola et al, 2015; Tuzcu et al, 2015; Cakmak et al, 2016), although some studies reported no difference in serum endocan levels (Yuksel et al, 2015). Other studies have shown a decrease in circulating endothelial progenitor cells as a marker of endothelial damage in PE women (Sakashita et al, 2014) (Table 1).…”
Section: Endothelial Dysfunction In Preeclampsiamentioning
confidence: 99%